The impact of home therapy interventions on treatment adherence and patient independence in haemophilia management in Assam, India - Dutta Anupam; Ngongpa Ajun; Gogoi Papari (The Journal of Haemophilia Practice, 2025)
Haemophilia is an inherited bleeding disorder requiring regular factor replacement therapy, often necessitating frequent hospital visits. Home therapy (HT) has emerged as a viable alternative, improving patient independence and adherence. This study evaluates the impact of a structured home therapy intervention at Assam Medical College and Hospital on treatment adherence, self-infusion rates, and quality of life among haemophilia patients.